2009
DOI: 10.1386/adch.8.2.169/1
|View full text |Cite
|
Sign up to set email alerts
|

Threshold concepts and the transport and product design curriculum: reports of research in progress

Abstract: In 2005, Coventry University was successful in bidding for Centre of Excellence in Teaching and Learning (CETL) funding from HEFCE, which led to the creation of the Centre of Excellence for Product and Automotive Design (CEPAD). This article discusses pedagogic research carried out by CEPAD to date, with a particular focus on the journey towards identifying one particular threshold concept in student transport and product design education. It also explores preliminary thoughts on how this ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…This is consistent with work done at Coventry University, where automotive design students were given the Purdue test but results did not correlate with student performance (Osmond et al 2009). These two results conflict with other examples of the Purdue test being used, where they are predictive of academic outcomes to a significant degree (Bodner and Guay 1997).…”
Section: Previous Educationsupporting
confidence: 85%
See 1 more Smart Citation
“…This is consistent with work done at Coventry University, where automotive design students were given the Purdue test but results did not correlate with student performance (Osmond et al 2009). These two results conflict with other examples of the Purdue test being used, where they are predictive of academic outcomes to a significant degree (Bodner and Guay 1997).…”
Section: Previous Educationsupporting
confidence: 85%
“…is considered a threshold concept (Meyer and Land 2012: 12). However, subsequent work (see Osmond et al 2009) found another threshold concept in this area related to the thinking processes that were needed before gaining skills and abilities. The threshold concept identified by Osmond et al was the toleration of design uncertainty -defined as the moment when 'a student recognizes that the uncertainty present when approaching a design brief is an essential, but at the same time routine, part of the design process'.…”
Section: Visualization Thinkingmentioning
confidence: 99%
“…Designers are always working at the periphery of a solution space where there is less coherence and more ambiguity and uncertainty. In fact, uncertainty in the design process is well documented in both the design literature and creativity literature (Osmond et al, 2009). During the design process, designers are required to navigate different variables that are characterized by some degree of uncertainty and are pushed to proceed amidst the vagueness of the process (Daalhuizen et al, 2009).…”
Section: Architectural Design Processmentioning
confidence: 99%
“…The literature identifies several methods for identifying threshold concepts. Both Osmond et al (2009) and Smith (2013) describe cases where thresholds in design education were identified by interviewing students about their experiences. Providing examples from economics and history, Entwistle (2009) notes that students can use concept maps to gain insight into how they perceive a subject such as which topics are seen as essential and difficult.…”
Section: Identification Of Learning Thresholdsmentioning
confidence: 99%